8.15 RAIL LAYING FOR HIGH-SPEED TRAIN MOVEMENTS - Begmatov Pardaboy Abdurakhimovich, Associate Professor Tadjibayev Sherzod Amirkulovich, Associate Professor Eshonov Farhod Faizullaxujayevich, Senior Lecturer (Innovative technologies in construction Scientific Journal, 2024)
The paper deals with a fluoroplastic under-rail gasket containing a base with a flat bearing surface in contact with the rail base, a flat inner bearing surface on high-speed traffic sections. Key words: track structure, earth bed, under-rail lining, fluoroplastic under-rail lining, ballast prism, fastenings, high-speed train traffic. A railway track is a complex engineering system that includes various elements such as rails, sleepers, fastenings, ballast layer, and subgrade. The performance of each of them as a whole and separately determines the reliability of the track and the safety of train traffic [1, 2, 3, 4]. Reducing maintenance costs of railway track structure has significantly increased the volume of both passenger and freight traffic in the world. The more intensive the traffic and the greater the tonnage transported on a section of track, the earlier the deterioration of track components occurs. The right measures to ensure long-term cost reductions and extend the service life of the rails help to significantly reduce the costs of track maintenance. The long-term utilisation of a track section depends crucially on the condition of the track. Special attention is paid to the most stressed components: ballast, sleepers and under-rail pads. With regard to the ultimate stresses, it can be said that only the values of the ultimate edge stresses in the rails and the allowable stresses under the pads on the sleeper, determined by the strength of the rail steel and the strength of the sleeper material, respectively, really exist. For the strength of the ballast layer, there are only estimated criteria [4].